A novel soft-switched single-phase grid-connected current-source inverter. Issue 1 (1st January 2017) - Pakdel, M.; Jalilzadeh, S.
Abstract: This paper represents a novel soft-switched grid-connected current-source inverter topology and an efficient control strategy using switching flow graph theory. The switching flow graph technique is a unique diagrammatic model and a convenient strategy for analyzing PWM switching converters. All power switches operate at zero-current-switching (ZCS) turn-off and zero-voltage-switching (ZVS) turn-on. As a result, commutation and switching power losses will be declined; furthermore, higher efficiency is achieved. The proposed topology and control strategy for soft-switched grid-connected inverter is analyzed theoretically and demonstrated experimentally.